Digitalization Drives Financial And Operational Outcomes In Small And Medium Enterprises: Digitalisasi Mendorong Capaian Keuangan Dan Operasional Pada Usaha Mikro Kecil Menengah - Vicha Dita Prasetyo; Yudi Nur Supriadi (Academia Open, 2026)
General Background Micro, small, and medium businesses represent the backbone of global economic frameworks, contributing significantly to employment and gross domestic product. Specific Background In the post-pandemic era, technological integration through electronic commerce, cloud computing, and artificial intelligence has become an essential strategy for business survival and continuous resilience. Knowledge Gap Although numerous studies explore technology adoption drivers, systematic syntheses focusing specifically on post-adoption business performance measurements during the 2020 to 2026 period remain scarce. Aims This systematic literature review synthesizes empirical evidence regarding how technological tools dictate the monetary, administrative, and marketing achievements of smaller commercial entities. Results The PRISMA-guided analysis of fifty peer-reviewed articles reveals that digital payment systems, social platforms, and electronic commerce consistently accelerate revenue growth, administrative efficiency, and market expansion. However, these technological advantages remain structurally constrained by widespread digital illiteracy, inadequate internet infrastructure, capital limitations, and cybersecurity vulnerabilities. Novelty This research comprehensively maps the conditional nature of digital transformation, establishing that technological deployment alone cannot generate optimal business success without simultaneous human capital and infrastructural readiness. Implications Policymakers and practitioners must prioritize literacy programs, secure financial inclusion frameworks, and robust internet access alongside technology adoption to realize sustainable competitive advantages. Highlights Electronic commerce and social platforms successfully accelerate revenue growth and market expansion. Structural barriers including inadequate internet infrastructure heavily restrict technological value realization. Systematic human capital development remains prerequisite for achieving sustainable competitive advantages. Keywords Digital Transformation; Business Performance; Systematic Literature Review; Artificial Intelligence; Competitive Advantage